2018
DOI: 10.1093/gerona/gly014
|View full text |Cite
|
Sign up to set email alerts
|

Apathy Is Associated With Greater Decline in Subjective, but not in Objective Measures of Physical Functioning in Older People Without Dementia

Abstract: In a Dutch cohort of older people without dementia, apathy was associated with more decline in self-reported, but not in objective physical functioning. Sex, age, and depression did not modify these associations. In older people with apathy, subjective decline may precede decline in physical performance tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…First, a recent population-based study in non-demented older persons using data of two ongoing cohort studies (LonGenity (Ayers et al, 2014) and Central Control of Mobility in Aging [CCMA (Holtzer et al, 2014)]) it was demonstrated that independent of depressive symptoms, apathy was more strongly associated with self-reported disability than with performance-based physical decline at follow up (Ayers et al, 2017). Second, we previously demonstrated similar results, using data from the Netherlands Study of Depression in Older persons (NESDO)-cohort; in older persons without dementia, apathy was associated with decline of self-reported physical functioning but not with decline in performance-based tests after two years, irrespective of the presence of depression (Henstra et al, 2018). These results imply that reduced goal-directed activity (apathy) has a stronger negative impact on self-reported than performance-based measures of functional status.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…First, a recent population-based study in non-demented older persons using data of two ongoing cohort studies (LonGenity (Ayers et al, 2014) and Central Control of Mobility in Aging [CCMA (Holtzer et al, 2014)]) it was demonstrated that independent of depressive symptoms, apathy was more strongly associated with self-reported disability than with performance-based physical decline at follow up (Ayers et al, 2017). Second, we previously demonstrated similar results, using data from the Netherlands Study of Depression in Older persons (NESDO)-cohort; in older persons without dementia, apathy was associated with decline of self-reported physical functioning but not with decline in performance-based tests after two years, irrespective of the presence of depression (Henstra et al, 2018). These results imply that reduced goal-directed activity (apathy) has a stronger negative impact on self-reported than performance-based measures of functional status.…”
Section: Introductionsupporting
confidence: 63%
“…Participants were asked to squeeze the dynamometer twice with their dominant hand in a standing position (Chung et al, 2014). For our analyses, the average of these two measurements was used (Henstra et al, 2018;2019). In order to combine the two performance-based tests, we divided the scores of both measures into quartiles and assigned a score of zero to the lowest functioning quartile, and a score of three to the highest functioning quartile.…”
Section: Assessment Of Performance-based Physical Functioningmentioning
confidence: 99%
“…Indeed, apathy is associated with lower levels of physical activity 38,39 and reduced walking speed, 17 both of which are signs of physical frailty 3 . However, the possibility that apathy may affect self‐reported disability more than actual performance‐based physical dysfunction should be considered 39 . Previous studies have also reported that apathy is associated with the risk of cardiovascular disease, 22,40 which is closely related to the development of frailty 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other NPS, apathy is associated with poorer outcome in pre-dementia populations. Cross-sectionally, apathy in non-demented groups is associated with executive dysfunction, 18,38 poorer quality of life, 39 olfactory disturbance, 40 subjective impairments in physical functioning, 41 impairment in instrumental activities of daily living, 39 and greater family caregiver burden. 42 Longitudinally, apathy in non-demented individuals is associated with functional decline, 43 slowed gait and frailty, 44 and incident cognitive decline and dementia.…”
Section: Apathy In Pre-dementia Statesmentioning
confidence: 99%